EVALUATION OF MODELS FOR ESTIMATING POTATO PRODUCTION TRENDS IN MAJOR STATES OF INDIA - Chandran, K. P.; Pandit, Arun; Pandey, N. K. (Potato Journal, 2013)
In the present study nonlinear mechanistic growth models, viz. monomolecular, logistic and Gompertz were used for describing potato production in major potato growing states, Uttar Pradesh, West Bengal and Bihar. Time series data from 1949-50 to 2003-04 were used. Levenberg-Marquardt procedure was used for estimation of the parameters. The study shows that logistic model could explain the production quite well. A comparative performance of the three states showed that Bihar has attained almost its potential production and West Bengal is having better scope for increasing the potato production in the coming years with the present trend. The study suggests to carry out region-specific micro-level studies to find out the areas where there exists scope to boost the farm level yield.